PENGARUH RISK PROFILE, EARNING DAN CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Fitri Ariyani; Indro Herry Mulyanto; Suratna Suratna (Jurnal Ilmu Administrasi dan Bisnis, 2019)
This study aims to determine the effect of risk profile, earnings and capital on firm value with profitability as an intervening variable in conventional banks listed on the Indonesia Stock Exchange (IDX) in 2011-2017. The sampling technique used was purposive sampling. The statistical method used is descriptive and inferential statistics, namely Generalized Structural Component Analysis (GeSCA) and Sobel test The results of the study show that the risk profile does not have a significant effect on firm value. Earning has a significant effect on firm value. Capital does not have a significant effect on firm value. capital does not have a significant effect on firm value. Capital does not have a significant effect on firm value. Risk profile has a significant effect on profitability. Earning has a significant effect on profitability. Capital has a significant effect on profitability. The mediation test shows that profitability is able to mediate the risk profile against the value of the company. Profitability is able to mediate earnings against company value and profitability is not able to mediate capital against firm value. Keywords: risk profile, earning, capital, profitability, firm value.